Policies to Promote Saving for Retirement : A Synthetic Overview - Vittas, Dimitri (World Bank, Washington, D.C., 2013)
The author argues that public and private pillars are essential for a well-functioning pension system. Public pillars, funded or unfounded, offer basic benefits that are independent of the performance of financial markets. Since financial markets suffer from prolonged, persistent, and large deviations from long-term trends, they cannot be relied on as the sole provider of pension benefits. Funded pillars provide benefits that are based on long-term capital accumulation and financial market performance. But they need to be privately managed to minimize dependence on public sector institutions and avoid government dominance of the economy and financial markets. The author focuses mainly on the promotion, structure, and regulation of funded pillars. He discusses the case for using compulsion and tax incentives, for exempting some categories of workers such as the very young (under 25), the very old (over the normal retirement age), the very poor (those earning less than 40 percent of the average wage), and the self-employed, and for offering a credit transfer to be added to individual capitalization accounts to encourage participation by lower-income groups. A robust regulatory framework with a panoply of prudential and protective rules covering "fit and proper" tests, asset diversification and market valuation rules, legal segregation of assets and safe external custody, independent financial audits and actuarial reviews, and adequate disclosure and transparency would be essential. An effective, proactive, well-funded, and properly staffed supervision agency would be necessary. Tight investment rules could initially be justified for countries with weak capital markets and limited tradition of private pension provision. But in the long run, adoption of the "prudent expert" approach with publication of "statements of investment policy objectives" (SIPOs) would be preferable and more efficient. Various guarantees covering aspects such as minimum pension levels and relative investment returns need to be provided to protect workers from aberrant asset managers and insolvency of annuity providers, but care must be taken to address effectively the risk of moral hazard. The author also argues for greater individual choice, including the creation of a dual regulatory structure. One part would involve heavy regulation with constrained choice of investment funds, limits on operating fees and on account switching, and strong government safeguards and guarantees. This would cater to those workers with low risk tolerance. The other part would be more liberal but based on strong conduct rules. It would offer greater choice of investment funds, allowing multiple accounts and liberal account switching, impose no limits on operating fees, and providing no or fewer state guarantees. This would cater to workers seeking a higher return and who are willing to tolerate a higher level of risk.